After the Text Byzantine Enquiries in Honor of Margaret Mullett (Taylor & Francis, 2022)
Byzantine Literature, Literature, Byzantine History, History, Poetry, Greek Literature, Byzantine Culture, Late Antique Literature, Medieval Literature, Classical Literature, and Hagiography
English
Keywords: Humanities; Byzantine Literature, Literature, Byzantine History, History, Poetry, Greek Literature, Byzantine Culture, Late Antique Literature, Medieval Literature, Classical Literature, and Hagiography